The architectural beginnings of Bogdan Bogdanović: The residential settlement of the Hydrotechnical Institute on the foothills of Avala - Janakova-Grujić Mare B. (Nasleđe)
The residential complex of the Hydrotechnical Institute at the foot of Avala mountain represents something of an idiosyncrasy of its era. Through its projection in the early 1950s, as a kind of garden village with a grape-like structure and free disposition, with houses made of hand-hewn stone, its architect Bogdan Bogdanović not only radically stepped out of the practice and theory of residential architecture and urbanism of the time, in opposition to the dogma of Socialist Realism, but manifested through its design a logical continuation and tangible result of his extensive reflections on the new Yugoslav architecture and a more humane society. This early work by Bogdanović stands as a vivid testament to the notions that the builder adhered to throughout his working life; through them, he came to replace mechanization with craftsmanship, ordinariness and typification with imagination, and blind modernization with tradition.